Multi‐atlas segmentation of the skeleton from whole‐body MRI—Impact of iterative background masking. Issue 5 (23rd October 2019) - Ceranka, Jakub; Verga, Sabrina; Kvasnytsia, Maryna; Lecouvet, Frédéric; Michoux, Nicolas; de Mey, Johan; Raeymaekers, Hubert; Metens, Thierry; Absil, Julie; Vandemeulebroucke, Jef
Abstract : Purpose: To improve multi‐atlas segmentation of the skeleton from whole‐body MRI. In particular, we study the effect of employing the atlas segmentations to iteratively mask tissues outside of the region of interest to improve the atlas alignment and subsequent segmentation. Methods: An improved atlas registration scheme is proposed. Starting from a suitable initial alignment, the alignment is refined by introducing additional stages of deformable registration during which the image sampling is limited to the dilated atlas segmentation label mask. The performance of the method was demonstrated using leave‐one‐out cross‐validation using atlases of 10 whole‐body 3D‐T1 images of prostate cancer patients with bone metastases and healthy male volunteers, and compared to existing state of the art. Both registration accuracy and resulting segmentation quality, using four commonly used label fusion strategies, were evaluated. Results: The proposed method showed significant improvement in registration and segmentation accuracy with respect to the state of the art for all validation criteria and label fusion strategies, resulting in a Dice coefficient of 0.887 (STEPS label fusion). The average Dice coefficient for the multi‐atlas segmentation showed over 11% improvement with a decrease of false positive rate from 28.3% to 13.2%. For this application, repeated application of the background masking did not lead to significant improvement of the segmentation result. Conclusions: A registration strategy, relying on the use of atlas segmentations as mask during image registration was proposed and evaluated for multi‐atlas segmentation of whole‐body MRI. The approach significantly improved registration and final segmentation accuracy and may be applicable to other structures of interest.